2020
DOI: 10.1177/1359105320913947
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic growth among 5195 adolescents at 8.5 years after exposure to the Wenchuan earthquake: Roles of post-traumatic stress disorder and self-esteem

Abstract: We evaluated the level of post-traumatic growth in a large sample of Chinese adolescent earthquake survivors ( n = 5195) and relationships among self-esteem, post-traumatic stress disorder, and post-traumatic growth. This cross-sectional study indicated that the prevalence of post-traumatic growth among adolescent survivors was 14.8 percent. Post-traumatic growth was independently associated with self-esteem, severity of exposures, and avoidance facets of post-traumatic stress disorder. Post-traumatic stress d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 57 publications
2
14
0
Order By: Relevance
“…This finding was consistent with previous findings that found that traumatic exposure was strongly associated with PTSD symptoms (Aisenberg et al, 2008;Laufer & Solomon, 2006;Tang et al, 2020b;Yang et al, 2020). The results also appeared to suggest that there was no relationship between objective pandemic exposure and growth, which was in contrast with results from other traumatic events, such as earthquakes (Tang et al, 2020c), domestic abuse (Cobb et al, 2006), or terrorist incidents (Laufer & Solomon, 2006), which suggested that young people may have experienced PTG without having greater pandemic exposure. One possible explanation is that unlike other traumatic events, COVID-19 is highly contagious and has several transmission routes that can potentially threaten everyone, even without having a direct exposure to the pandemic.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This finding was consistent with previous findings that found that traumatic exposure was strongly associated with PTSD symptoms (Aisenberg et al, 2008;Laufer & Solomon, 2006;Tang et al, 2020b;Yang et al, 2020). The results also appeared to suggest that there was no relationship between objective pandemic exposure and growth, which was in contrast with results from other traumatic events, such as earthquakes (Tang et al, 2020c), domestic abuse (Cobb et al, 2006), or terrorist incidents (Laufer & Solomon, 2006), which suggested that young people may have experienced PTG without having greater pandemic exposure. One possible explanation is that unlike other traumatic events, COVID-19 is highly contagious and has several transmission routes that can potentially threaten everyone, even without having a direct exposure to the pandemic.…”
Section: Discussionsupporting
confidence: 90%
“…A total score of 61 or higher (cut-off point = 61) has been found to indicate significant PTG (Rodríguez-Rey et al, 2017). The Chinese version of the Posttraumatic Growth Inventory has been used in previous studies on Chinese adolescents and had shown satisfactory psychometric properties (Tang et al, 2020c). The internal consistency of the present study was found to be excellent (Cronbach's α = 0.963).…”
Section: Ptgsupporting
confidence: 48%
“…The positive changes after experiencing stress events, including increasing personal strength, identifying new possibilities, increasing enjoyment of life, improving interpersonal relationships and positive mental changes, and these changes could be consistently found across different types of trauma [9,10]. It should be noted that PTG is not a return to baseline following trauma exposure, but rather it could create an increased appreciation for life in general, more meaningful interpersonal relationships, an increased sense of personal strength, changed priorities, and a richer existential and spiritual life [11].…”
Section: Introductionmentioning
confidence: 90%
“…Additionally, a study found that a significant number of survivors developed PTSD after six or more months after the initial traumatic event (26). Studies have demonstrated that people continued to suffer from PTSD 8 years after the earthquake (27)(28)(29)(30)(31)(32). These studies focused on factors related to PTSD, such as alexithymia (27), post-traumatic growth (28), self-esteem (29), depression (30), suicidal behaviors (31), and community support (32).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that people continued to suffer from PTSD 8 years after the earthquake (27)(28)(29)(30)(31)(32). These studies focused on factors related to PTSD, such as alexithymia (27), post-traumatic growth (28), self-esteem (29), depression (30), suicidal behaviors (31), and community support (32). However, all of them were cross-sectional studies and none of them focused on delayed-onset PTSD.…”
Section: Introductionmentioning
confidence: 99%